(untitled) (CIPEEX, 2022)
&NBSP;INTRODUCTION: THE CARDIORESPIRATORY STOP (CRP) &NBSP;IS DEFINED AS THE SUDDEN CESSATION OF USEFUL VENTRICULAR MYOCARDIAL ACTIVITY, ASSOCIATED WITH LACK OF BREATHING, AND HAS NOT RECEIVED DUE ATTENTION FROM THE HEALTH TEAM. IT IS AN EVENT THAT OCCURS FREQUENTLY IN THE ICU, SINCE THESE UNITS ASSIST SEVERELY ILL PATIENTS WITH MARKED HEMODYNAMIC INSTABILITY, REQUIRING THE TEAM TO IMPROVE THEIR COGNITIVE, MOTOR SKILLS AND UPDATE ON RESUSCITATION MANEUVERS (FERREIRA ET AL., 2012 ). IN ORDER FOR CARE TO HAPPEN PROPERLY, QUICKLY AND SAFELY, THE MULTIPROFESSIONAL TEAM MUST BE PREPARED TO ENSURE SUCCESS. IN ADDITION, CRP REQUIRES PROMPT ASSISTANCE TO AVOID INJURY AND BETTER PATIENT RECOVERY. THE QUALITY OF CARE ALLOWS FOR PREVENTION AND UNDESIRABLE EVENTS, WHICH MAY COMPROMISE THE PATIENT’S HEALTH (MOURA ET AL., 2012). OBJECTIVE: THE OBJECTIVE OF THIS STUDY WAS TO DEMONSTRATE THE IMPORTANCE OF NURSING CARE IN AN EMERGENCY SITUATION TO THE PATIENT VICTIM OF CARDIORESPIRATORY ARREST AT THE INTENSIVE CARE UNIT THROUGH THE LITERATURE. METHOD: THIS IS AN INTEGRATIVE REVIEW OF THE LITERATURE. WITH THE PURPOSE OF GATHERING, ANALYZING AND SYNTHESIZING EXISTING STUDIES ON THE PROPOSED THEME. FOR THE DEVELOPMENT OF THE STUDY, THE SEARCH FOR ORIGINAL SCIENTIFIC ARTICLES PUBLISHED IN THE DATABASES: LATIN AMERICAN AND CARIBBEAN LITERATURE IN HEALTH SCIENCES (LILACS), MEDICAL LITERATURE ANALYSIS AND RETRIEVAL SYSTEM ONLINE (MEDLINE), PUBMED CENTRAL, SIX YEARS (2011-2015), AVAILABLE IN FULL IN PORTUGUESE, ENGLISH AND SPANISH. THE DESCRIPTORS IN HEALTH SCIENCES (DECS) WERE USED: PCR, NURSING CARE; ICU. INCLUDED IN THE INTEGRATIVE REVIEW WERE STUDIES THAT OBEYED THE FOLLOWING CRITERIA: ARTICLES THAT PRESENT THE CONCEPT OR DEFINITION ADOPTED FOR CARDIOPULMONARY ARREST IN BRAZIL, WHERE THE CHARACTERISTICS OF THE SAMPLE ARE CLEAR, AS WELL AS THE COUNTRY, CITY AND HOSPITAL SECTOR IN THAT DATA COLLECTION HAS OCCURRED. THEN, THE FIVE METHODOLOGICAL MOMENTS OF EXECUTION WERE CARRIED OUT ACCORDING TO MENDES (2008), DETERMINATION OF THE GUIDING QUESTION, EXPLORATORY READING, READING COMPREHENSION AND ANALYSIS AND CONTENT ANALYSIS. 6 ARTICLES WERE SELECTED. RESULTS: AFTER THE ANALYSIS OF CONTENT EMERGED THE CATEGORIES: PROCEDURES RECOMMENDED IN THE SERVICE OF PCR; KNOWLEDGE AND DIFFICULTIES FOUND BY THE NURSING TEAM. OF CATEGORY II APPEARED TWO SUBCATEGORIES BEING THESE: SUBCATEGORY I - KNOWLEDGE OF THE TEAM AGAINST THE PCR; SUBCATEGORY II - DIFFICULTIES FOUND BY NURSING PROFESSIONALS. CONCLUSION: THE RESULTS OBTAINED AFTER THE ANALYSIS SHOWED THAT THE DETERMINANTS OF THE SURVIVAL OF THE VICTIMS OF CRP ARE KNOWLEDGE OF THE HEALTH PROFESSIONAL, RELATED TO THE BASIC LIFE SUPPORT AND ADVANCED LIFE SUPPORT, THE THEORETICAL-PRACTICAL KNOWLEDGE OF THE NURSE ABOUT THE MANEUVERS AND THE EARLY DIAGNOSIS OF CARDIORESPIRATORY ARREST. IT IS NECESSARY THAT THE NURSE PARTICIPATES IN TRAINING AND UPDATES AND THAT THERE ARE INVESTMENTS IN THEIR KNOWLEDGE, BECAUSE THE POSITIVE RESULT CAN SAVE LIVES.